1996
DOI: 10.1103/physreve.54.r4516
|View full text |Cite
|
Sign up to set email alerts
|

Products of random matrices and investment strategies

Abstract: A simple stochastic model of investment based on communication theory is introduced and analyzed in detail. We solve it exactly in a simple case and we use a weak disorder expansion to deal with the small fluctuations of the capital between two consecutive trading periods. Some possible generalizations are also discussed. ͓S1063-651X͑96͒52011-8͔PACS number͑s͒: 02.50. Le, 05.20.Ϫy Let us consider an investor, whose aim is to increase a given capital Z by investing it in several stocks i (iϭ1, . . . ,M) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…This scaling behavior does not hold when the cross-correlations between companies are destroyed, suggesting the existence of correlations between companies -as occurs in strongly interacting physical systems where power-law correlations at the critical point result in scale-invariant properties. Recent studies of the cross-correlation matrix using methods of random matrix theory [32][33][34] also show the existence of correlations that are present through a wide range of time scales from 30 mins [34] up to 1 day [32,33]. These studies [32][33][34] show that the largest eigenvalue of the cross-correlation matrix corresponds to correlations that pervade the entire market, and a few other large eigenvalues correspond to clusters of companies that are correlated amongst each other.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This scaling behavior does not hold when the cross-correlations between companies are destroyed, suggesting the existence of correlations between companies -as occurs in strongly interacting physical systems where power-law correlations at the critical point result in scale-invariant properties. Recent studies of the cross-correlation matrix using methods of random matrix theory [32][33][34] also show the existence of correlations that are present through a wide range of time scales from 30 mins [34] up to 1 day [32,33]. These studies [32][33][34] show that the largest eigenvalue of the cross-correlation matrix corresponds to correlations that pervade the entire market, and a few other large eigenvalues correspond to clusters of companies that are correlated amongst each other.…”
Section: Discussionmentioning
confidence: 95%
“…A direct way of analyzing the cross-correlations is by computing the cross-correlation matrix [32][33][34]. Here, we take a different approach, by analyzing the distribution of returns as a function of market capitalization.…”
Section: Cross-correlationsmentioning
confidence: 99%
“…1 -4 A wide range of problems have been studied, for example, the shape of the distribution of price changes, 5 theoretical models of financial markets, 6,7 portfolio selection and optimization, 8,9 and wealth distribution, [10][11][12] to name just a few.…”
Section: Introductionmentioning
confidence: 99%
“…It can be shown that the above equation can be derived from a Hamiltonian [5], [6] which describes an elastic chain, or a directed polymer, in a periodic potential (alternatively attractive and repulsive). The Hamiltonian reads…”
mentioning
confidence: 99%
“…The first step consists in the search of a self-consistent expression for the partition "wave" function. The full calculation has been already carried out in a general hypercubic lattice [6]:…”
mentioning
confidence: 99%